(untitled) (Homiletic, 2009)
This article describes one of the first large qualitative studies of people who listen to sermons (“Listening to Listeners”), summarizes the major publications that have come from that study, reflects on the effects of the study in the larger preaching community, meditates on criticism of the study, and reports on efforts to bring listeners and preachers into dialogue about preaching.